Natural killer cells induce eosinophil activation and apoptosis. - Ali Awad (Public Library of Science (PLoS), 2014)
Eosinophils are potent inflammatory cells with numerous immune functions, including antigen presentation and exacerbation of inflammatory responses through their capacity to release a range of largely preformed cytokines and lipid mediators. Thus, timely regulation of eosinophil activation and apoptosis is crucial to develop beneficial immune response and to avoid tissue damage and induce resolution of inflammation. Natural Killer (NK) cells have been reported to influence innate and adaptive immune responses by multiple mechanisms including cytotoxicity against other immune cells. In this study, we analyzed the effect of the interaction between NK cells and eosinophils. Co-culture experiments revealed that human NK cells could trigger autologous eosinophil activation, as shown by up-regulation of CD69 and down-regulation of CD62L, as well as degranulation, evidenced by increased CD63 surface expression, secretion of eosinophil cationic protein (ECP) and eosinophil derived neurotoxin (EDN). Moreover, NK cells significantly and dose dependently increased eosinophil apoptosis as shown by annexin V and propidium iodide (PI) staining. Direct contact was necessary for eosinophil degranulation and apoptosis. Increased expression of phosphorylated extracellular signal-regulated kinase (ERK) in cocultured eosinophils and inhibition of eosinophil CD63 expression by pharmacologic inhibitors suggest that MAPK and PI3K pathways are involved in NK cell-induced eosinophil degranulation. Finally, we showed that NK cells increased reactive oxygen species (ROS) expression by eosinophils in co-culture and that mitochondrial inhibitors (rotenone and antimycin) partially diminished NK cell-induced eosinophil apoptosis, suggesting the implication of mitochondrial ROS in NK cell-induced eosinophil apoptosis. Pan-caspase inhibitor (ZVAD-FMK) only slightly decreased eosinophil apoptosis in coculture. Altogether, our results suggest that NK cells regulate eosinophil functions by inducing their activation and their apoptosis.